1957
DOI: 10.1139/y57-041
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Detection of Atypical Forms of Human Serum Cholinesterase. Determination of Dibucaine Numbers

Abstract: Cases with atypical esterase activity were found by determining esterase inhibition in numerous sera. A suitable inhibitor was the local anaesthetic dibucaine (cinchocaine, TN Nupercaine, Perkain). A good discrimination between typical and atypical sera was obtained under the following conditions: The esterase activity of human serum diluted 1:100 was measured with a recording spectrophotometer at 240 mμ. The substrate was 5 × 10−5 M benzoylcholine dissolved in M/15 phosphate buffer, pH 7.4. The concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
3

Year Published

1968
1968
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(88 citation statements)
references
References 1 publication
2
83
0
3
Order By: Relevance
“…The frequency of people with atypical alleles in other parts of the world is about 1 in 3000 (Kalow 1992). In our study, the overall frequency of the atypical allels was 0.5% (5 of 1000 healthy blood donors from five different ethnic groups).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The frequency of people with atypical alleles in other parts of the world is about 1 in 3000 (Kalow 1992). In our study, the overall frequency of the atypical allels was 0.5% (5 of 1000 healthy blood donors from five different ethnic groups).…”
Section: Discussionmentioning
confidence: 43%
“…For example, Singh et al (1997) found similar results in 193 subjects (111 males and 82 females) in northern Indian adults, but Jensen et al (1995), in a survey of more than 6000 people in Denmark, found a significantly lower plasma cholinesterase activity in females than in males. Although it is not possible to discriminate between the various BChE genotypes using activity tests alone, Kalow and Genest (1957) developed a simple method for determining who was a carrier of atypical BChE. The dibucaine number is the percent of inhibition of hydrolysis of the substrate in the presence of 10 µmol/L of dibucaine.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important condition as it is treatable, provided specialized post operative management and nursing care is administered in the intensive care unit. Patients with this deficiency have a marked sensitivity to suxamethonium and similar cholinesterase inhibiting drugs, this leads to prolonged post anaesthesia apnoea and death may follow administration of these drugs [5]. In a study conducted by Cerf 80% of patients experiencing prolonged neuromuscular blockade following Mivacurium had butyrylcholinesterase deficiency of genetic origin [6].…”
Section: Discussionmentioning
confidence: 99%
“…Further testing can be carried out using the dibucaine (2-butoxy-N-[2-(diethylamino) ethyl] quinoline-4-carboxamide) inhibition test, which produces a value known as the dibucaine number (DN). This method (16) involves a PNP-based color reaction that is read at 405 nm. It can be defined as the percentage by which cholinesterase is inhibited by dibucaine.…”
Section: Cholinesterasesmentioning
confidence: 99%